Administrasi Sekolah di SD Negeri 27 Anak Air, Lubuk Buaya, Kec. Koto Tangah, Kota Padang, Sumatera Barat - Nadia Putri Nasution; Rusdinal; Hade Afriansyah (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This research aims to analyze the implementation of the Lewin Model in organizational development from the perspective of administrative staff at SD Negeri 27 Anak Air, Lubuk Buaya, Koto Tangah District, Padang City, West Sumatra. The Lewin Model, consisting of three stages unfreezing, moving (changing), and refreezing is a classic framework that remains relevant for managing planned change in educational institutions. This qualitative descriptive study employed in-depth interview methods and field observations with administrative staff at the school. The results indicate that SDN 27 Anak Air applies the Lewin Model particularly in managing major changes such as curriculum transitions, while routine organizational development activities tend to follow the Action Research Model. Implementation of the Lewin Model shows varying effectiveness across the three stages: unfreezing involves coordination meetings and socialization from the education office; moving is characterized by dynamic adaptation among teachers with varying support needs; and refreezing is achieved after approximately one year when the new curriculum becomes established practice and drives teacher innovation. This research concludes that the Lewin Model is effectively applied for managing major transformations, though its implementation requires strong leadership commitment, adequate training, continuous support systems, and active participation from all school members to ensure successful and sustainable organizational change